Atezolizumab for the treatment of breast cancer. Issue 3 (3rd March 2020) - Reddy, Sangeetha M.; Carroll, Emma; Nanda, Rita
ABSTRACT: Introduction : In March 2019, atezolizumab became the first immune checkpoint inhibitor to receive a breast cancer-specific approval. Based on a significant improvement in progression-free survival as well as a 10-month improvement in overall survival (on interim analysis) seen in the IMpassion 130 trial, the combination of atezolizumab and nab-paclitaxel was approved for patients with unresectable locally advanced or metastatic triple-negative breast cancer (TNBC). Areas covered : This article reviews current data and ongoing research on atezolizumab for the treatment of breast cancer. Results of atezolizumab monotherapy trials in the context of other early immune checkpoint blockade trials in breast cancer are discussed as well as data from combination clinical trials with chemotherapy in both early-stage and metastatic breast cancer. We focus on the safety and efficacy analyses from the phase III IMpassion trial that led to FDA and EMA approval of atezolizumab and nab-paclitaxel in patients whose tumor tested positive for PD-L1 by the Ventana SP142 companion diagnostic immunohistochemical assay. Expert opinion : The FDA and EMA approvals of atezolizumab mark an important advance for treatment of metastatic TNBC. However, ongoing investigations need to define better biomarkers of response, determine resistance mechanisms, and identify strategies to increase response rates.